PENGARUH INTEGRITAS, KOMPETENSI, DAN PROFESIONALISME TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN AKUNTANSI PADA PT. BANK MANDIRI (PERSERO) TBK MANADO - Rani, Falentina K. G.; Lambey, Linda; Pinatik, Sherly (Universitas Sam Ratulangi, 2018)
The succeed of company is determined by the existing of human resources. Furthermore, high qualified competences and professionalism of human resources can improve work productivity. This research is aimed to know the influence of integrity, competences, and professionalism to accounting employeesâ€™ productivity at PT. Bank Mandiri (Persero) Tbk Manado. This is a quantitative causal research. Data were collected by questionnaires and interviews. This study employed 36 respondents. Data were analysed by multiple linear regression analysis. Regression equation result is Y = -13,193 + 0,590X1 + 0,239X2 + 0,817X3 + e. Results show that integrity, competences, and professionalism influence employeesâ€™ productivity.Â Keywords: Integrity, Competences, Professionalism, and Work Productivity